INFLUENCE OF THE LECTIN LACTOBACILLUS DELBRUECKII ssp. BULGARICUS ON ACTIVITY OF THE PROCESS OF PHAGOCYTOSIS - A. S. Dolmashkina (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The effect of Lactobacillus delbrueckii ssp. bulgaricus on the activity of macrophages — peritoneal (PMP) and alveolar (AMP), isolated from the body of white mice at 1, 3, 5, 7 days after the introduction of lectin, in the process of phagocytosis of bacteria Staphylococcus aureus 209-P. In the course of the studies, it was shown that by 6 hours the activity of PMP and AMP isolated within 24 hours after lectin administration had increased by 3.4 and 2.9 times. The PMP and AMP, isolated from the mice for 3 days, showed the greatest activity after 6 hours of incubation with bacterial cells in 1.6 and 2 times in comparison with the control. On day 5, PMP and AMP showed the greatest activity by 6 hours in the process of phagocytosis compared with the control, respectively, in 2.2 and 2.4 times. At day 7, only AMP had the highest activity after 30 minutes of incubation with bacteria 1.5 times in comparison with the control in the process of phagocytosis in vitro by S. aureus 209-P. With respect to PMP, no changes were observed compared to the control. The analysis of the obtained data showed that the activity of macrophages isolated from the organism of mice injected with lectin on days 1, 3, 5 significantly differed from the control values at the final stages of the phagocytosis process of S. aureus 209-P. It can be assumed that the lectin interacting with the surface structures of PMP and AMP on the 1st, 3rd, 5th day of the experiment promotes a more short-term process of adhesion of bacterial cells in phagocytosis. To evaluate the specificity of lectin interaction with receptor structures of macrophages, experiments were conducted with a protein that did not have lectin properties-bovine serum albumin-BSA and lectin blocked by specific carbohydrates. It was shown that the phagocytic activity of macrophages in the presence of BSA was similar to control and did not differ significantly from it. BSA did not influence the completion of bacterial phagocytosis by macrophages. When studying the interaction of lectin blocked by specific carbohydrates on the phagocytic activity of macrophages, there was a slight increase in phagocytic activity against PMP, after 6 hours of phagocytosis and a slight decrease after 0.5 hours, 1 hour and 24 hours of phagocytosis. For AMP, the lectin blocked by a mixture of carbohydrates was similar to the control values. The results obtained made it possible to speak of the specific binding of lectin L. delbrueckii ssp. bulgaricus with surface AMP receptors. However, with respect to PMP, a small activity of macrophages in the process of phagocytosis was observed, which indicates the specific and non-specific binding of lectin L. delbrueckii ssp. bulgaricus with surface TMF receptors. It can be assumed that, at the molecular level, L. delbrueckii ssp. bulgaricus, in addition to a specific interaction with the receptor structures of PMP, can participate in a variety of nonspecific reactions. Thus, the lectin L. delbrueckii ssp. bulgaricus increased the adhesive ability of macrophages of mice, significantly influenced the completeness of the phagocytosis process of bacterial cells. A specific interaction of L. delbrueckii ssp bulgaricus with surface AMP receptors, both specific and non-specific interactions were observed with respect to PMP.